Coaching to Enhance Thai Forensic Police Officer’s Self-efficacy, Meaningful Work, and Job Crafting: A Case Study of the Office of Police Forensic Science - Suramanee, Pornpavee; Rucktum, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
For the past two decades, forensic science has been playing essential role in criminal investigation in Thailand. It has been praised as a game changer for criminal justice. The work of Thai forensic police officers has profoundly altered how police investigated crimes since it can provide evidence for answering crucial questions like Who? What? When? Where? Why? and How? more objectively and expeditiously among other available tools. Unfortunately, due to the nature of the behind-the-scenes type of work, Thai forensic police officers perceive themselves as just scientists working in some backroom laboratory who has no real influence nor decision making power in the overall investigation process. Thus, this study aims to explore these issues in the hope of enhancing the Thai forensic police officers’ (FPO) self-efficacy (SE), meaningful work (MW), and job crafting (JC). The study applied self-efficacy theory, meaning in work based on job characteristics theory and job crafting model as the theoretical framework. Three hypotheses were derived to evaluate significant difference between Pre-ODI and Post-ODI based on self-efficacy, meaningful work, and job crafting. Both qualitative and quantitative data were collected and used for analysis. They were obtained from 30 forensic police officers from eight different functions stationed in ten provinces using stratified sampling technique. Organization development interventions (ODI) were executed over the period of two months using individual coaching techniques, and questionnaires and interviews as instruments. Reflexive thematic analysis paired samples t-test, and Wilcoxon signed-rank test were chosen to analyze the data. Findings revealed that self-efficacy and meaningful work showed significant differences after the coaching intervention, whereas job crafting failed to exhibit any statistical significance.